Association between dietary factors and brown adipose tissue volume/18F-FDG uptake in young adults. Issue 4 (April 2021) - Jurado-Fasoli, Lucas; Merchan-Ramirez, Elisa; Martinez-Tellez, Borja; Acosta, Francisco M.; Sanchez-Delgado, Guillermo; Amaro-Gahete, Francisco J.; Muñoz Hernandez, Victoria; Martinez-Avila, Wendy D.; Ortiz-Alvarez, Lourdes; Xu, Huiwen; Arias Téllez, María José; Ruiz-López, María Dolores; et al.
Summary: Objective: To study the association between usual dietary factors (dietary energy density, nutrient intake, food group consumption, and dietary pattern) and brown adipose tissue (BAT) volume/ 18 F-fluorodeoxyglucose ( 18 F-FDG) uptake after personalized cold exposure in young healthy adults. Methods: A total of 122 young adults (n = 82 women; 22.0 ± 2.1 years old; 24.8 ± 4.8 kg/m 2 ) took part in this cross-sectional study. Dietary factors were measured via a food frequency questionnaire and three non-consecutive 24 h recalls. Dietary energy density (foods and caloric beverages included) and macronutrient intakes were subsequently estimated using EvalFINUT® software, food group consumption was estimated from the food frequency questionnaire, and different dietary patterns and quality indices were determined according to the reference methods. BAT volume, BAT 18 F-FDG uptake, and skeletal muscle 18 F-FDG uptake were assessed by static 18 F-FDG positron-emission tomography and computed tomography (PET-CT) scans after a 2 h personalized exposure to cold. Results: A direct association was detected between dietary energy density and BAT Standardized Uptake Value (SUV)mean (β = 0.215; R 2  = 0.044; P = 0.022), and between ethanol consumption and BAT volume (β = 0.215; R 2  = 0.044; P = 0.022). The a priori Mediterranean dietary pattern was inversely associated with BAT SUVmean and SUVpeak (β = −0.273; R 2  = 0.075; P = 0.003 and β = −0.255; R 2  = 0.066; P = 0.005 respectively). In addition, the diet quality index for a Mediterranean diet and a pro-inflammatory dietary pattern (as determined via the dietary inflammatory index) were directly associated with BAT SUVmean and SUVpeak (SUVmean: β = 0.238; R 2  = 0.053; P = 0.013 and β = 0.256; R 2  = 0.052; P = 0.012 respectively; SUVpeak: β = 0.278; R 2  = 0.073; P = 0.003 and β = 0.248; R 2  = 0.049; P = 0.016 respectively). After controlling for multiplicity and possible confounders (sex, the evaluation wave and BMI), all the detected associations persisted. Conclusion: Dietary factors are slightly associated with BAT volume and/or 18 F-FDG uptake after a personalized cold exposure in young adults. Our results provide an overall picture of the potential relationships between dietary factors and BAT-related variables in humans.